2020
DOI: 10.3390/su12125202
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of Digitalization on Business Values: The Results of Examining Values of People Management in a Digital Age

Abstract: The European Union (European Parliament) understands industry 4.0 as a term for an environment of fast transformations of production systems and products. The basic characteristic of the change in the methods of creating added value in the conditions of the fourth industrial revolution is digitalization. Digitalization changes people management in two stages. The first stage is the adaptation of systems to the integration of physical inputs into digital systems, and the second stage is the redefinition of valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 65 publications
1
20
0
3
Order By: Relevance
“…Digitalization changes people management in two stages. The first stage is the adaptation of systems to the integration of physical inputs into digital systems, and the second stage is the redefinition of values for the internal and external customer (Blštáková et al, 2020). This is in line with research conducted by Pertiwi & Nurhikmah (2018) entitled the effect of digitalization system changes on employee performance with the result that there is a significant influence between digitalization system and employee performance.…”
Section: Introductionsupporting
confidence: 72%
“…Digitalization changes people management in two stages. The first stage is the adaptation of systems to the integration of physical inputs into digital systems, and the second stage is the redefinition of values for the internal and external customer (Blštáková et al, 2020). This is in line with research conducted by Pertiwi & Nurhikmah (2018) entitled the effect of digitalization system changes on employee performance with the result that there is a significant influence between digitalization system and employee performance.…”
Section: Introductionsupporting
confidence: 72%
“…The relationship between knowledge sharing and incentives was further supported by studies of Slovak authors such as Ližbetinová et al (2020), Stachová et al (2020) and Blštáková et al (2020) who found that there were significant changes in the stimulus system that encouraged individuals to share their knowledge, especially through technology. The forthcoming Fourth Industrial Revolution provides comprehensive systems and tools aimed at promoting information sharing at the individual, team, and organization levels, as well as at a cluster level.…”
Section: Literature Reviewmentioning
confidence: 89%
“…If it is possible to start from the above results, changes can be expected particularly in the timing of both concepts. With the comprehensive digitization of business processes [77,78], planned audits and operational controls will move toward continuous implementation. This has already been confirmed by the theories of Kaban [79] and Bieliaieva [80] about the audit or those of Christensen et al [81] about control.…”
Section: Discussionmentioning
confidence: 99%